International legal argument in the Permanent Court of International Justice : the rise of the international judiciary - Spiermann, Ole. (New York : Cambridge University Press, 2005)
"The book draws on hitherto unpublished archival material left by judges and other persons involved in the work of the Permanent Court, giving insights into many of its most important decisions and the individuals who made them (Huber, Anzilotti, Moore, Hammerskjold and others). At the same time it examines international legal argument in the Permanent Court, basing its approach on a developed model of international legal argument that stresses the intimate relationships between international and national lawyers and between international and national law."--BOOK JACKET.
A project of international justice -- The basis of international law -- The double structure of international legal argument -- Revisiting the Permanent Court -- The foundational period, 1922-1924 -- An international lawyer's approach, 1925-1930 -- An international lawyer's approach, 1931-1940 -- The legacy of the Permanent Court.
Includes bibliographical references (pages 425-468) and index.
Keywords: Permanent Court of International Justice; Cour permanente de justice internationale; Permanent Court of International Justice; 2; 1900-1999; Geschichte; International courts -- History -- 20th century; Tribunaux internationaux -- Histoire; CIJ = Cour internationale de justice; Histoire; Juridictions internationales; 2; International courts; Permanent Hof van Internationale Justitie; Internationaal recht; Argumentatie; History